(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
The article examines the phenomenon of vowel modification in connected speech, a central aspect of phonetic and phonological studies in English linguistics. Vowel modification refers to the alterations that vowels undergo when words are spoken in continuous speech, as opposed to their citation form in isolation. The study explores the primary processes influencing these changes, including vowel reduction, assimilation, elision, and coarticulation. Emphasis is placed on the role of stress patterns, speech tempo, and phonetic environment in shaping vowel quality, length, and intensity. The article also analyzes the functional significance of vowel modification in achieving speech fluency and intelligibility. Empirical examples are drawn from native English speech to illustrate common patterns of connected speech, highlighting both systematic tendencies and context-dependent variations. The findings contribute to a better understanding of natural spoken English, with implications for language teaching, pronunciation training, and computational modeling of speech.